2014
DOI: 10.6026/97320630010460
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking Based Screening of Plant Flavonoids as Dengue NS1 Inhibitors

Abstract: Dengue infection has turned into a serious health concern globally due to its high morbidity rate and a high possibility of increase in its mortality rate on the account of unavailability of any proper treatment for severe dengue infection. The situation demands an urgent development of efficient and practicable treatment to deal with Dengue virus (DENV). Flavonoids, a class of phytochemicals present in medicinal plants, possess anti-viral activity and can be strong drug candidates against viruses. NS1 glycopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Moreover, the research studies also rationalized that the novel ribavirin analogs presumably may not cause hemolytic anemia to the patients supposed to administrate them as the compounds showed weak affinities towards the JAK2 enzyme playing essential roles in erythropoiesis. Qamar et al [15] postulate through a computational approach that flavanoids (Deoxycalyxin A, 3,5,7,3',4'pentahydroxyflavonol-3-O-beta-D-galactopyranoside, (3R)-3',8-Dihydroxyvestitol, Sanggenon O, Epigallocatechin gallate and Chamaejasmine) inhibited the NS1 (by blocking through the Asparagin 130 glycosylation site), an important regulatory element in the replication processes of dengue viruses. Ariza et al [16] showed that molecular dockings between curcumin and RdRp domain of the NS5 protein, also a key element in the viral replication, with a binding energy of-6.2 Kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the research studies also rationalized that the novel ribavirin analogs presumably may not cause hemolytic anemia to the patients supposed to administrate them as the compounds showed weak affinities towards the JAK2 enzyme playing essential roles in erythropoiesis. Qamar et al [15] postulate through a computational approach that flavanoids (Deoxycalyxin A, 3,5,7,3',4'pentahydroxyflavonol-3-O-beta-D-galactopyranoside, (3R)-3',8-Dihydroxyvestitol, Sanggenon O, Epigallocatechin gallate and Chamaejasmine) inhibited the NS1 (by blocking through the Asparagin 130 glycosylation site), an important regulatory element in the replication processes of dengue viruses. Ariza et al [16] showed that molecular dockings between curcumin and RdRp domain of the NS5 protein, also a key element in the viral replication, with a binding energy of-6.2 Kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…Peptide models (antigenic determinants) were docked against their respective HLA-B7 allele through Molecular Operating Environment (MOE) tool to analyze their inhibitory potential. Protocol for molecular docking using MOE has already been reported in various studies involving the antiviral discovery against dengue non-structural proteases [ 30 – 32 ]. Docking protocol used in those studies involves removal of already bound peptide, protonation, energy minimization followed by removal of water molecules.…”
Section: Methodsmentioning
confidence: 99%
“…The NS1 protein is involved in several functions throughout the viral life cycle and immune evasion and can be used for DENV detection. Some studies have reported that the NS1 protein can serve as a drug target for DENV [54,55]. However, although the binding region of this protein has been predicted using computational tools, this has not been experimentally confirmed.…”
Section: Viral Target For Phenolic Lipid Compoundsmentioning
confidence: 99%